Detection of Vibrio campbellii and V. parahaemolyticus carrying full-length pirABVp but only V. campbellii produces PirVp toxins - Vicente A. (2020)
Acute hepatopancreatic necrosis disease (AHPND) is a newly emerging disease of penaeid shrimps caused by a unique strain of Vibrio species that carries a plasmid harboring PirABVp-binary toxin gene. Since the first outbreak in 2009, the diseases have been reported in a number of countries in Asia, America, and Latin America. In the present study, we obtained 51 bacterial isolates recovered from five AHPND suspected shrimp farms in South America for PCR diagnosis using AP4 nested PCR method. There were 3/51 isolates (34, 36 and 43) from two farms which tested positive by AP4 primers targeting PirABVp toxin genes. The detection results were also confirmed by duplex pirABVp PCR assay. Subsequently, integrity of full length pirABVp genes in the three positive isolates was revealed by sequencing analysis. Bacterial species identification by ldh-specific PCR combined with multilocus sequencing analysis (MLSA) revealed that the two isolates 36 and 43 are V. parahaemolyticus while the isolate 34 is V. campbellii. Surprisingly, pirABVp mRNA transcript was detected from only V. campbellii 34 while that of V. parahaemolyticus 36 and 43 were undetectable. The results coincide with Western blot analysis that only V. campbellii 34 produces both PirAVp and PirBVp toxins while two isolates of V. parahaemolyticus pirAVp+ and pirBVp+ express neither PirAVp nor PirBVp toxins. Experimental challenge revealed that PirABVp-containing V. campbellii 34 and atypical V. parahaemolyticus isolates 36 and 43 were pathogenic to shrimp. Massive cell sloughing of hepatopancreatic tubule epithelial cells, characteristic of AHPND, was observed from shrimp exposed to isolate 34 while isolates 36 and 43 caused extensive collapsed hepatopancreatic tubule epithelia. The findings in this study indicated that there is a proportion of Vibrio isolates harboring intact pirABVp that were tested positive by PCR but did not produce AHPND PirABVp toxins. We thus suggested that investigation of pirABVp expression at transcriptional and translational levels as well as bioassay is required for confirmation of AHPND-causing Vibrio strain.